2021
DOI: 10.1136/bmj.n2213
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and biomarkers of alpha linolenic acid and risk of all cause, cardiovascular, and cancer mortality: systematic review and dose-response meta-analysis of cohort studies

Abstract: Objective To examine the associations between dietary intake and tissue biomarkers of alpha linolenic acid (ALA) and risk of mortality from all causes, cardiovascular disease (CVD), and cancer. Design Systematic review and meta-analysis of prospective cohort studies. Data sources PubMed, Scopus, ISI Web of Science, and Google Scholar to 30 April 2021. Study selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 91 publications
1
51
0
3
Order By: Relevance
“…Omega-3 fatty acids are a family of essential and biologically relevant fatty acids that belong to the PUFAs, being mostly available in nuts, alfa-linolenic acid (ALA), which is metabolised to eicosapentaenoic acid and docosahexaenoic acid, with anti-inflammatory properties. In this regard, a recent meta-analysis published in 2021 by Naghshi et al [30] found that a high intake of ALA was associated with a reduced risk of mortality from all causes, CVD and coronary heart diseases. Additionally, the nuts contain phytosterols, which have an inverse relationship with blood cholesterol levels [31] and other bioactive compounds with antioxidant properties such as polyphenols and vitamin E, all of which play an important role in the prevention of cardiovascular disease [32].…”
Section: Adherence To Recommended Nut Consumptionmentioning
confidence: 99%
“…Omega-3 fatty acids are a family of essential and biologically relevant fatty acids that belong to the PUFAs, being mostly available in nuts, alfa-linolenic acid (ALA), which is metabolised to eicosapentaenoic acid and docosahexaenoic acid, with anti-inflammatory properties. In this regard, a recent meta-analysis published in 2021 by Naghshi et al [30] found that a high intake of ALA was associated with a reduced risk of mortality from all causes, CVD and coronary heart diseases. Additionally, the nuts contain phytosterols, which have an inverse relationship with blood cholesterol levels [31] and other bioactive compounds with antioxidant properties such as polyphenols and vitamin E, all of which play an important role in the prevention of cardiovascular disease [32].…”
Section: Adherence To Recommended Nut Consumptionmentioning
confidence: 99%
“…Moreover, common obesity-associated features such as dyslipidemia, hypertension, and insulin insensitivity [12][13][14] that lead to the development of metabolic syndrome and increase the risk for the development of cardiovascular and other diseases such as type 2 diabetes and cancer are not found in all obese subjects [15,16]. ALA may play an important role in obesity and related diseases as well as obesity-associated comorbidities [17][18][19], but its effects are generally inconsistent and understudied, so future Molecules 2022, 27, 4471 2 of 23 well-designed controlled clinical trials could be needed. In addition to the listed features associated with obesity, the ectopic accumulation of the fat in the liver is often present, and it can lead to the development of non-alcoholic fatty liver disease (NAFLD) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to explore whether ALA has similar effects on the risk of HF. However, although previous studies showed that dietary patterns that included ALA-rich foods may reduce the risk of cardiovascular disease (10,11), the association between ALA and HF was unclear. The Physicians' Health Study has found that dietary ALA intake level showed an inverse trend towards an association with HF, (12) while other studies did not find a similar association (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%